Evaluación de tierras para el desarrollo de proyectos ecoturísticos en la provincia de Sumapaz (Cundinamarca) (2021)
The purpose of the present work is to evaluate suitable the development of ecotourism projects, establishing the criteria and the necessary variables to identify these areas, defining the methodology and the union of criteria to obtaining as a final result the zoning of suitable areas for the development of ecotourism projects in the Sumapaz province.